COW HOUSING UNDER SANITARY AND HYGIENIC CONDITIONS OF MILK PRODUCTION - Tomashevsky , E.; Varpikhovskyi, R. (EurasianUnionScientists, 2021)
It is established that in the stall period (November - March) the microclimate of the cowshed is 4.0 points, which complies with the engineering design conditions, to improve the parameters it is necessary to optimize the conditions regarding the concentration of harmful gases in the air and microbial contamination. Well-timed faeces disposal and air ventilation control will optimize these parameters. It is proven that the thermal balance of the building depends on the created conditions of comfortable keeping of cows and their number in the building, as well as heat loss through the enclosing structures: gates, windows, ceiling, floor and walls, the thermal balance in the cowshed is made for the outside temperature of (-4,3 ° С). Since sanitary and hygienic conditions of cow housing do not meet the optimal design and technological regime, and the amount of microorganisms in the air of the room is above norm and negatively affects the health of cattle, it is necessary to implement integrated elements of technology in the process of commercial milk production and rationalize the schedule while maintaining standards of technological design.